Cooperative Learning as an Innovative Method in Teaching English - Kenjayev Azizbek; Sharipova Sabokhat (Research Parks Publishing LLC, 2021)
In this article was given some data about helpful learning as an imaginative strategy in instructing jargon. Having experience and creating ability with this kind of acquiring regularly works with casual and base learning. Agreeable learning is an instructive methodology, which expects to sort out study hall exercises into scholarly and social learning encounters.